Imputation accuracy is robust to cattle reference genome updates. (16th December 2014) - Milanesi, M.; Vicario, D.; Stella, A.; Valentini, A.; Ajmone‐Marsan, P.; Biffani, S.; Biscarini, F.; Jansen, G.; Nicolazzi, E. L.
Summary Genotype imputation is routinely applied in a large number of cattle breeds. Imputation has become a need due to the large number of SNP arrays with variable density (currently, from 2900 to 777 962 SNPs). Although many authors have studied the effect of different statistical methods on imputation accuracy, the impact of a (likely) change in the reference genome assembly on imputation from lower to higher density has not been determined so far. In this work, 1021 Italian Simmental SNP genotypes were remapped on the three most recent reference genome assemblies. Four imputation methods were used to assess the impact of an update in the reference genome. As expected, the four methods behaved differently, with large differences in terms of accuracy. Updating SNP coordinates on the three tested cattle reference genome assemblies determined only a slight variation on imputation results within method.